Odpowiedzi

2010-04-12T15:34:48+02:00
A) V=abc / :bc
V/bc=a

b) L=2(a+b+b)/ :2
L/2=a+2b
L/2 -2b =a

c)V=½ abh /*2
2V=abh /:bh
2V/bh = a

d)V=⅓πa²h /*3
3V= πa²h /:πh
3V/πh =a² /√
√3V/πh =a

e)P=2(ab+bc+ac) /:2
P/2 =ab+bc+ac
P/2 -bc = a(b+c) /: b+c
P/2 -bc / b+c = a

f)P=(2a+3b/2)h /:h
P/h = 2a+3b/2
(P/h-3b/2 ) /2 =a

2010-04-12T15:36:29+02:00
A) V=abc /:bc
V/bc=a
b) L=2(a+b+b)
L=2a+4b
2a=L-4b/:2
a= 1/2L-2b
c) V=1/2 abh /*2
2V=abh /bh
2V/abh=a
d) V=1/3π a²h /:πh
V=1/3a² /*3
a²=3V:πh
e)P=(2a+bc+ac) /bc
P/bc=2a+ac /:c
(P/bc)/c= 2a+a
f) P=P=(2a+3b/2)h /:h
P/h = 2a+3b/2
(P/h-3b/2 ) /2 =a
Najlepsza Odpowiedź!
2010-04-12T15:37:47+02:00
A)V=abc
a=V/(bc)

b)L=2(a+b+b)
L=2a+4b
2a=L-4b
a=(L-4b)/2

c)V=½ abh
2V=abh
a=(2V)/(bh)

d)V=⅓πa²h
3V=πa²h
a²=(3V)/(πh)
a=√[(3V)/(πh)] (lub) a=-√[(3V)/(πh)]

e)P=2(ab+bc+ac)
P=2ab+2bc+2ac
P-2bc=2a(b+c)
2a=(P-2bc)/(b+c)
a=(P-2bc)/(2(b+c))

f)P=(2a+3b/2)h
P/h= 2a + 3b/2
2P/h= 4a+ 3b
(2P)/h -3b = 4a
a=(2P)/(4h) -3b/4
a=P/(2h) - 3b/4


1 1 1